Treatment of saline solutions using Air Gap Membrane Distillation: Experimental study - Alkhudhiri, Abdullah (2013)
Air Gap Membrane Distillation (AGMD) has been implemented for four different salts. The permeate fluxes of sodium chloride (NaCl), magnesium chloride (MgCl2), sodium carbonate (Na2CO3), and sodium sulphate (Na2SO4) are measured at different feed concentrations and different operating parameters using Polytetrafluoroethylene (TF200) membrane. The influence of membrane pore size is investigated for the different salts. Also, the effect of feed concentration, feed temperature, coolant temperature and feed flow rate on permeate flux is studied. The flux declines as the concentration of salt and coolant temperatures increase, and increases as the feed temperature and flow rate increase. Moreover, the energy consumption was measured at different salt concentrations for the different membrane pore size and was found to be independent of membrane pore size, and salt type.